Study of Sequential Cytotoxicity using 2,6-Diphenyl Piperidin-4-One Scaffold - L. Jadhav, Rahul; S. Magdum, Chandrakant (Asian Journal of Chemistry, 2012)
Novel compounds were synthesized in order to evaluate the theory of sequential cytotoxicity, which seeks to exploit the view that various cancer cells are particularly susceptible to successive attacks by cytotoxic agents. The series of analogous which lacking of olefinic bond and one olefinic bond were synthesized, which will predicted to be less cytotoxic than the compounds having two or three olefinic bonds. All the synthesized compounds have been screened for cytotoxic property by SRB-assay method against leukemic and colon cancer cell lines at four different concentrations. The results revealed that the predictions made regarding the viability of the theory were fulfilled. In addition, the significant properties of compound 5 and 6 towards cancerous cell lines, confirms their usefulness in serving as lead molecules for further development.